2015
DOI: 10.1038/ncomms7509
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling of a homeobox gene cluster by multiple independent gene reunions in Drosophila

Abstract: Genome clustering of homeobox genes is often thought to reflect arrangements of tandem gene duplicates maintained by advantageous coordinated gene regulation. Here we analyse the chromosomal organization of the NK homeobox genes, presumed to be part of a single cluster in the Bilaterian ancestor, across 20 arthropods. We find that the ProtoNK cluster was extensively fragmented in some lineages, showing that NK clustering in Drosophila species does not reflect selectively maintained gene arrangements. More impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…These results show that, apart from the duplication of NK6 in onychophorans (or the onychophoran subgroup containing E. rowelli ), onychophorans and tardigrades possess an identical set of eight NK cluster genes, whereas NK7 is missing in both taxa. However, the presence of NK7 in the genomes of several arthropods [Additional file 1 ; 23 , 58 ] as well as other bilaterians [Additional file 1 ; 24 , 59 ] suggests that a complete “protoNK cluster” [ 7 , 23 , 60 , 61 ] consisting of nine genes was present in the last common ancestor of Panarthropoda and that NK7 was most likely lost in the onychophoran and tardigrade lineages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results show that, apart from the duplication of NK6 in onychophorans (or the onychophoran subgroup containing E. rowelli ), onychophorans and tardigrades possess an identical set of eight NK cluster genes, whereas NK7 is missing in both taxa. However, the presence of NK7 in the genomes of several arthropods [Additional file 1 ; 23 , 58 ] as well as other bilaterians [Additional file 1 ; 24 , 59 ] suggests that a complete “protoNK cluster” [ 7 , 23 , 60 , 61 ] consisting of nine genes was present in the last common ancestor of Panarthropoda and that NK7 was most likely lost in the onychophoran and tardigrade lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Like the Hox and ParaHox genes, the NK genes are typically arranged in one or several clusters. However, the NK cluster shows a much higher degree of rearrangement due to extensive breakup, inversion and reunion events in different taxa [ 22 , 23 ]. Based on the composition of the NK cluster in insects, combined with the information from chordates, it has been deduced that the ancestral bilaterian NK cluster comprised nine genes, namely NK1 , NK3 , NK4 , NK5 , NK6 , NK7 , Msx , Lbx and Tlx [ 7 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of homeobox genes first in Drosophila and then in vertebrates has given rise to renewed interest in the concept of discontinuous evolution and macroevolution [47]. Phylogenic studies of the vertebrate Hox cluster and linked genes have suggested that the homeobox genes organization in malleable gene clusters occurred through processes of large-scale chromosomal rearrangements that reshape gene organization over evolutionary time [48,49].…”
Section: Chromoanagenesis and Saltational Evolutionmentioning
confidence: 99%
“…The NK cluster also presents one of the clearest examples yet of the uncertainty that we have about the dynamics and polarity of evolutionary change in homeobox gene clusters: ancient clusters breaking apart vs. dispersed genes coming together (perhaps multiple times independently such that clusters might not be homologous). A recent analysis of NK gene locations across the densely sampled drosophilids revealed that these genes can come together secondarily by multiple intrachromosomal rearrangements over relatively short evolutionary periods, i.e., within genera rather than across phyla, at least for genes that are already linked on the same chromosome (Chan et al, 2015). In contrast, the presence of NK clusters in sponges, insects and now hemichordates pushes us to assume that there was an ancestral NK cluster formed via the types of tandem duplications Many of these families are more ancient than the PDA.…”
Section: The Nk Cluster: An Ancestral Cluster Breaking Apart or Dispementioning
confidence: 99%